PRODUKSI DAN UJI AKTIVITAS ENZIM KITINASE DARI ISOLAT BAKTERI TERMOFILIK B1211 ASAL AIR PANAS BORA - Jaya Hardi; Jusman Jusman; Abdul Rahman Razak; Silva Silva (KOVALEN: Jurnal Riset Kimia, 2016)
This research aims to production of chitinase from thermophylic bacteria that living in Bora hot spring  and to determine of chitinase extracts activity. The research was began with rejuvenated of B1211 bacteria isolates on MSM agar media.  The B1211 isolates was used to production of chitinase extracts on MSM broth media with chitin colloidal concentration of 0.25%, 0.5%, 1%, 2%, 4% and incubation temperature of 30oC (rt), 37oC, 50oC, and 60oC for 3 days. The chitinase activity were analyzed based on N-acetyl-D-glucosamine standard. The results was showed that B1211 bacteria isolates is potential isolate for production chitinase. The highest activity of chitinase from B1211 bacteria isolates of 0.75 U/mL for chitin colloidals concentration of 1% and temperature of 60oC.Keywords : Bora, hot spring, bacteria, thermophylic, B1211 isolates, chitinase.